(untitled) - Neilson, Alasdair H. (Boca Raton, 2008)
Offering an updated and expanded version of a previous work, Organic Chemicals: An Environmental Perspective, Neilson and Allard, both affiliated with IVL Swedish Environmental Research Institute, examine a wide range of compounds as well as abiotic and microbiological reactions mediated by microorganisms, emphasizing the pathways used and the broad classes of enzymes involved. The authors begin by reviewing abiotic and biotic reactions and looking at the significance of a range of environmental determinants. They then introduce experimental procedures for establishing the structure of metabolites using isotopes and physical methods. They detail the biochemical reactions involved in the biodegradation of major aliphatic, carbocyclic aromatic, and heterocyclic compounds. The book concludes with material on bioremediation.
Keywords: Aquatic organisms,Organic water pollutants,Sinh thái học; Effect of water pollution on,Environmental aspects